A Systematic Review of Exit Exams in Higher Education: The Upsides and Downsides - Samson Worku Teshome (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2025)
Exit exams in higher education have both upsides and downsides. This review examines their impact using the PRISMA methodology. It analyzes 22 empirical studies published between 1994 and 2024. The search covered databases like Google Scholar, ERIC, PubMed, Scopus, and Web of Science. A thematic narrative synthesis was used to evaluate the findings. Exit exams improve accountability and standardize assessments. They align curricula with learning goals. This ensures consistent educational quality across institutions. Students gain job-ready skills, enhancing employability. Exams also promote critical thinking and inclusivity. However, downsides exist. High-stakes exams increase student stress and anxiety. They may lead to